Agrowaste compost as a component of substrates for ornamental plants = Compost de agroresiduos como componente de sustratos para plantas ornamentales - Gutierrez, Agustina; Orden, Luciano; Postemsky, Pablo; Iocoli, Gastón Alejandro; Mockel, Gabriela; Marinangeli, Pablo (ASAHO, 2022)
The formulation of substrates for ornamental plants in containers implicates a compromise between physicochemical and biological characteristics, costs, andenvironmental impact for the use of peat. A way to optimize this relationship is by using local components. This work proposes the elaboration of a substrate based on Sphagnum peat and perlite, complemented with compost from regional agricultural residues as a possible replacement for a commercial substrate. The growth and development of Impatiens walleriana and Antirrhinum majus L. plants were compared in containers with different substrates: commercial (SC), peat/perlite 9/1 (TP), pure compost (C), and four TP/C mixtures (v:v): 8/2, 6/4, 4/6 and 2/8. The parameters evaluated in Impatiens walleriana were foliar area, number of flowers and accumulated biomass and in Antirrhinum majus L., plant height, nodes per plant, chlorophyll content (SPAD), estimated flowering percentage and accumulated biomass. A physicochemical characterization was carried out for the substrates, and it showed that the main limitation of incorporating compost is the increase of electric conductivity and pH, but with good management it is possible to increase its proportion in the mixtures. The TP/C 8/2 treatment obtained the best results among the mixtures, significantly exceeding the rest. No significant differences were found with the commercial substrate for most of the parameters measured in both ornamental species. The TP/C 8/2 treatment is the more economical and sustainable option due to the reduction in the use of peat and the recovery of wastes.